Morphological Characteristics and Biomass Production Brassica rapa var. Marco During the Dry Season - Nafiatul Umami; Yogi Sidik Prasojo; Miftahush Shirothul Haq (ANIMAL PRODUCTION, 2022)
This study aimed to determine morphological, adaptability, and biomass production of Brassica rapa var. Marco planted in Karang Malang, Yogyakarta, Indonesia during the dry season. The seeds used were the introduced feed plants Brassica rapa var. Pillar from Crop Mark Seed Company New Zealand. The seeds were spread in 1 m2 plots. Each plant had 3 replicates at the end of rainy season (March) and defoliation in September. The variables observed in this study were plant growth and plant morphology. Also, biomass production, dry matter (DM), and organic matter (OM) content of each plant were statistically analyzed by independent sample t-test. Biomass production was taken from the first and second defoliation (first regrowth). The plant morphology showed that the plants could develop well. The plant growth showed that dry matter production of Brassica rapa var. Pillar was 1.15 tonnes/ha/year. The first and second defoliation of Brassica rapa var. Marco produced 1.61 tonnes/ha (DM 9.89% and OM 79.99) and 2.47 tones/ha (DM 9.17% and OM 84.82%), respectively, indicating significant difference. It can be concluded that the varieties of Brassica rapa var. Marco can thrive when planted during the dry season in Yogyakarta.